Neodymium: Yag Laser Capsulotomy Rates Following Implantation of Silicon and Acrylic Intraocular Lenses - Muhammad Kamran Saeed, Muhammad Kashif Hanif, Syed Abid Hassan Naqvi, Uzma Ansari, Haseeb Ahmed Khan (Pakistan Journal of Ophthalmology, 2009)
Purpose. The objective of this study is to compare the frequency of Neodymium YAG laser capsulotomy in eyes receiving silicon foldable posterior chamber intraocular lenses with those receiving acrylic foldable posterior chamber intraocular lenses. Material and Methods. This Comparative study was carried out at Ophthalmology Department C.M.H. Karachi from August 2007 to August 2008. Sixty patients were included in this study. Thirty patients were included in-group A who opted for acrylic foldable IOLs and thirty patients in group B who opted for Silicon foldable IOLs. All the patients underwent phacoemulsification procedure with 3.2mm clean corneal self-sealing incision. Then they were followed for one year. During follow up on each visit visual acuity was taken, slit lamp examination was performed for posterior capsular opacification and cases selected for Nd YAG laser capsulotomy having posterior capsular opacification sufficient to cause decrease in visual acuity more than 2 lines. Chi-square test was used to calculate frequency of YAG laser capsulotomy in both groups. Results. In group A one patient was diagnosed as having clinically significant posterior capsular opacification (PCO) enough to reduce visual acuity of two lines (snellen chart) requiring Nd: YAG laser capsulotomy at the end of one year and in Group B three patients were diagnosed as having clinically significant posterior capsular opacification (PCO) enough to reduce visual acuity of two lines (snellen chart) requiring Nd:YAG laser capsulotomy at the end of one year. Conclusion. PCO and frequency of Nd: YAG laser capsulotomy was more common in eyes receiving silicone IOLs than eyes receiving acrylic IOLs.